Analisis tingkat kepuasan penelpon terhadap kualitas pelayanan telephone operator di hotel conrad bali - Priti Shanti, I Gusti Agung Ayu Nitia; Suarka, Fanny Maharani; Pertiwi, Putu Ratih (Jurnal Kepariwisataan dan Hospitalitas; Vol 1 No 2 (2017): Vol.1,No.2,2017, 2017)
Telphone operators are required to provide quick services in responding to any request or provide information desired. Telphone operators provides service of incoming call or outgoing call. When do the job not all service goes smoothly as expected. Telphone operators are required to be able to provide the right action when receive complaints. In the general conclusion quality of service will goes smoothly when the telphone operator follows all of the standard procedure and be oriented of the callers satisfaction.  This report aims to analyze the quality service of telphone operator in handling incoming call and outgoing call at Hotel Conrad Bali and analyze callers satisfaction level on service quality of telephone operator in Hotel Conrad Bali. Data collection techniques in this report used observation, interviews, questionnaires, literature studies, and documentation. The technique of determining the informant in this report used purposive sampling technique by determining the base informant, key informant, and expert informant. The sampling technique in this report used purposive sampling technique. Respondents were determined by using slovin formula with 76 respondents. Data analysis techniques in this report using descriptive qualitative analysis techniques and quantitative descriptive analysis with likert scale approach and analysis by using cartesius diagram. The results in this report showed that the operator service quality analysis in handling incoming call and outgoing call at Conrad Bali Hotel had total average satisfaction rate of 98.49%, it’s that mean in the general caller was satisfied with service by telphone operator. Service in incoming call is better than outgoing call.